IMPROVING MATHEMATICS LEARNING OUTCOMES IN UNITS OF TIME USING WALL CLOCK MEDIA AT SDN TUNJUNG 4 - Indah Nurul Arishanti; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Mathematics is a subject that is always considered difficult by most students. To be able to make students more interested and understand mathematical concepts, the teacher should present mathematics lessons as attractively as possible and change abstract mathematical concepts to be more concrete. The purpose of this study was to determine the increase in students' mathematics learning outcomes in unit time when learning was assisted by the use of wall clock media. This research is classroom action research with participatory collaborative research type. The research model used is a research model from Stephen Kemmis and Mc Taggart with data collection methods in the form of tests and interviews. The results showed that there was an increase in the number of students who completed learning from the original 30% before being given action, to 95% in the second cycle. Therefore, it can be concluded that learning mathematics in unit time using wall clock media can improve student learning outcomes.